Kestrel rugged environmental meter [library of things] (Nielsen-Kellerman, Kestrel, 2015)
"Multi-functional environmental meter for researchers, technicians, farmers, site managers and other professionals. Provides accurate measurement and logging of indoor and outdoor conditions." Measures air speed, temperature, relative humidity, volume air flow, evaporation rate, humidity ratio, heat stress index, wet bulb temperature, station pressure, barometric pressure, altitude, density altitude, air density, relative air density, delta T.